Teachers' Perceptions of Drug Prevention Programs in Elementary Schools in Pamekasan: Challenges and Solutions - Zainullah, Zainullah; Hasyim Abd. Qadir, Moh. (LP2M IAI Al-Khairat Pamekasan, 2024)
This study aims to analyze teachers' perception of drug prevention programs in elementary schools in Pamekasan, focusing on the challenges faced and solutions that can be implemented. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation involving teachers and principals as research subjects. The results of the study show that most teachers understand the importance of this program, but face obstacles in the form of lack of training, limited learning resources, lack of parental support, and limited time in the curriculum. The proposed solutions include increasing teacher training, providing relevant learning media, and increasing parental and community involvement. This research emphasizes the need for collaboration between schools, families, and other stakeholders to increase the effectiveness of drug prevention programs in the primary education environment.